The role of posyandu cadres is o peran kader posyandu dalam pengaplikasian stimulasi deteksi intervensi dini tumbuh kembang anak: PERAN KADER POSYANDU DALAM PENGAPLIKASIAN STIMULASI DETEKSI INTERVENSI DINI TUMBUH KEMBANG ANAK DI PUSKESMAS MONCONGLOE KAB. MAROS - Putri umar, Sandini; dewi, S.Kep.,Ns.,M.Kes, indra; A, S.Kep.,Ns.,M.Kep, Alfiah (STIKES Nani Hasanuddin, 2022)
The role of posyandu cadres is one of the spearheads who play a role in the approach to child development disorders because they meet directly with the community and are in the middle so that posyandu cadres are expected to be able to provide information early. Growth and development is an increase in the ability of the body to function in a regular pattern and is thought to be the result of the processes of cells, organs and tissues of the body. The purpose of this study was to determine the role of Posyandu cadres in the application of stimulation detection of early intervention for child development at the Moncongloe Health Center, Kab. Maros. This study uses a descriptive observational approach. Sampling using the technique of Simple Random Sampling, obtained 50 respondents. Data was collected using a questionnaire and analyzed univariately. The conclusion in this study was to know the description of the role of posyandu cadres in the application of SDIDTK. Keywords : SDIDTK, The Role of Posyandu Cadres